The Underdiagnosis of Chronic Kidney Disease in Patients with a Documented Estimated Glomerular Filtration Rate and/or Urine Albumin–Creatinine Ratio in Germany - Karel Kostev; Martina Lang; Sven-Oliver Tröbs; Sophia Urbisch; Maximilian Gabler (Medicina)
Background and Objectives: The underdiagnosis of chronic kidney disease (CKD) is a critical issue worldwide. This present study aimed to explore the CKD subpopulation regarding underdiagnosed CKD in individuals with a pathological estimated glomerular filtration rate (eGFR) and/or urine albumin–creatinine ratio (UACR) values in Germany. Materials and Methods: This analysis used data from the IQVIATM Disease Analyzer database and included adult outpatients with at least two pathological consecutive eGFR and/or UACR values, documented at least 60 days apart between October 2018 and September 2023 in 758 general practices. According to the 2024 KDIGO clinical practical guidelines, CKD was defined based on both eGFR and UACR values. UACR values were used when no pathological eGFR values were documented. The main outcome of the study was the proportion of patients with a documented CKD in the total population as well as in defined subgroups. Results: A total of 113,996 CKD patients (mean age: 76.5 (SD: 10.1) years; 60.2% female; 71.5% with mildly to moderately, 21.1% with moderately to severely, and 4.6% with a severely decreased eGFR value; and 1.0% with end-stage kidney disease) were available for analyses. CKD diagnosis was documented in 46.9% of CKD patients and was more frequent in male than in female patients (53.3% versus 42.7%). The highest proportion was observed in patients with heart failure (57.0%), followed by patients with type 2 diabetes (52.7%). In patients without diabetes and heart failure, CKD was documented in 38.2%. The proportion of CKD diagnoses increased with decreasing eGFR values, from 22.0% in patients with nonpathological eGFR but moderately or severely increased UACR to 87.7% in patients with end-stage kidney disease. Conclusions: The study provides valuable insights into the subpopulation of underdiagnosed CKD patients among a large patient population. These results underscore the need for improved screening, timely diagnosis documentation, and treatment strategies for CKD, particularly among high-risk populations. Moreover, it raises the need to increase awareness of micro- and macroalbuminuria as diagnostic criteria for CKD independent of eGFR.